Urban areas have lower species richness, but maintain functional diversity: insights from the African Bird Atlas Project. (9th April 2021) - Lee, Alan Tristram Kenneth; Ottosson, Ulf; Jackson, Colin; Shema, Sidney; Reynolds, Chevonne
Abstract : High human population growth and rapid urbanisation, particularly in Africa, have led to an increased interest in the impacts of this land-use change on bird communities. The African Bird Atlas Project, where species presence lists are collected in pentads, is a valuable source of data with which to explore the extent of these impacts. Here, for the first-time, we test for differences in species richness patterns across 50 matched pentad pairs from sub-Saharan Africa classified as either urban (or semi-urban) and rural. We found that species richness was lowest in pentads classified as urban (mean ± SD: 132 ± 59 species), compared with rural (172 ± 54). However, species richness was similar, compared with rural pentads, when levels of urbanisation were maintained at intermediate levels (semi-urban: 141 ± 69). Surprisingly, we found no significant differences in functional diversity measures between any land-use categories. Across most major dietary guilds (carnivores, herbivores, insectivores, granivores) species richness was lower in urbanised pentads and species were often small. However, the overall biomass of these guilds was similar between urbanised and non-urbanised areas, indicating the presence of common urban exploiter species. This resulted in no differences in functional diversity overall. Pollinators and piscivores showed little difference in metrics between rural and urban pentads. According to a model of the functional traits we consider, an African urban exploiter species is best described by being a scavenger, and less likely to be a habitat specialist, but fill a variety of niches. The urban spatial planning implications are that rare and range-restricted species in proximity to cities, as well as large bird species, will require particular attention and conservation measures as African cities continue to expand. Species richness could be maintained with intermediate levels of urban infrastructure development.